Playing Hopscotch to Develop Gross Motor Skills in School-Age Children with Moderate Intellectual Disabilities at SLB Negeri Slawi - Anisa Oktiawati; Ita Nur Itsna; Jumrotun Ni’mah; Siti Amalia (Yayasan Cendekiawan Digital Indonesia, 2024)
Children with intellectual disabilities are unable to follow regular school programs, but they possess abilities that can be developed through education, which includes determining appropriate service programs based on the needs and conditions of children with intellectual disabilities. According to data from the 2018 Basic Health Research, the province of Central Java has 20,150 children with disabilities aged 5-17 years. A preliminary study conducted by the researcher at SLB N Slawi found that there were 307 students with disabilities. Gross motor skills involve activities or tasks that require coordination of muscles and nerves. The game of hopscotch can help children practice moving their bodies, improve agility, and enhance dexterity during play. The purpose of this research is to examine the implementation of playing hopscotch to develop gross motor skills in school-age children with moderate intellectual disabilities. This research is descriptive with a case study approach and has been reviewed through an ethical test. Data were collected through interviews, observation, physical examinations, and documentation. The TMGD (Test of Gross Motor Development) instrument and observation sheets were used. After the intervention, conducted 3 times with 30-minute sessions, the results showed effectiveness in the form of improvements in gross motor skills after each hopscotch therapy session. The TMGD instrument and observation sheets were used for measurement. Children with moderate intellectual disabilities are advised to engage in hopscotch therapy once a day for 30 minutes.